STRATEGI PEMASARAN PRODUK TAHU DALAM MENINGKATKAN MINAT PELANGGAN DI DAERAH SARI REJO, SUMATERA UTARA - Diva Aulia Ramadani Perangin-angin; Ella Tri Puspita; Fahmi Abdillah; Zainarti Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the marketing strategies of tofu products implemented by small businesses in the Sari Rejo area, North Sumatra, and how these strategies contribute to increasing customer interest. Tofu is a daily food staple with high consumption in urban areas. However, high levels of competition require businesses to develop innovative marketing strategies that align with the characteristics of the local community. Using a descriptive qualitative approach, this study describes the marketing practices used and the factors that support the success of tofu product marketing in the area. The results indicate that effective marketing strategies include improving product quality, implementing competitive pricing, an interpersonal marketing approach, utilizing simple digital media, and a direct-to-consumer distribution strategy. This combination of strategies has been proven to increase customer interest and expand market reach.